2023
DOI: 10.1186/s12905-023-02506-w
|View full text |Cite
|
Sign up to set email alerts
|

Experience and severity of menopause symptoms and effects on health-seeking behaviours: a cross-sectional online survey of community dwelling adults in the United Kingdom

Abstract: Background Almost all women will experience menopause, and the symptoms can have a severely detrimental impact on their quality of life. However, there is limited research exploring health-seeking behaviours and alternative service design or consultation formats. Group consultations have been successfully deployed in perinatal and diabetic care, improving accessibility and outcomes. This cross-sectional online survey was conducted to explore women’s personal experiences of menopause, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 52 publications
0
8
0
1
Order By: Relevance
“…20 In addition, seeking care can permit proactive help and inform women of symptoms that they otherwise would not realize were treatable, further improving quality of life. 20 In addition to prescribing therapies, our clinicians validate symptoms, discuss lifestyle and behavioral approaches, and encourage healthy habits. As such, the antidepressant alone group did show symptom improvement; however, this must be viewed more holistically, as the additional therapies and specialized care may have played a role in these outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 In addition, seeking care can permit proactive help and inform women of symptoms that they otherwise would not realize were treatable, further improving quality of life. 20 In addition to prescribing therapies, our clinicians validate symptoms, discuss lifestyle and behavioral approaches, and encourage healthy habits. As such, the antidepressant alone group did show symptom improvement; however, this must be viewed more holistically, as the additional therapies and specialized care may have played a role in these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, any consultation occurring at a specialized clinic that involves seeking professional care may improve outcomes. Healthcare professionals can prescribe treatment but also recommend lifestyle changes, which can benefit symptom management 20 . In addition, seeking care can permit proactive help and inform women of symptoms that they otherwise would not realize were treatable, further improving quality of life 20 …”
Section: Discussionmentioning
confidence: 99%
“…The findings from this study confirm previous research around women's experiences of menopause; the symptoms they experience and the impact these can have on their quality of life. [6][7][8][9] What this study adds is an understanding that the barriers to accessing effective support for these symptoms are still prevalent, are fuelled by misperceptions and lack of knowledge, and operate at all levels of the healthcare system. The Women's Health Strategy for England published in August 2022, which drew on survey responses from almost 100,000 women and over 400 written submissions from organisations and experts in healthcare, also found that accessing appropriate services for menopause care is difficult.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Previous research has concentrated on quantifying the number of women who experience menopausal symptoms, the impact of their symptoms, and whether they seek healthcare advice, are offered and, ultimately, take HRT. [5][6][7][8][9] This study aimed to complement and enrich these findings by digging beneath the surface to understand why so few women request help or are offered treatment. The study focuses on the barriers that prevent women from approaching GPs, the barriers preventing GPs from offering treatment and why women refuse HRT.…”
Section: Introductionmentioning
confidence: 99%
“…Menopausal symptoms affect an estimated 1.5 million women worldwide every year (Fouad et al, 2021). As the world's population ages, it is estimated that by 2030, 1.2 billion females worldwide will have gone through menopause or perimenopause (Huang et al, 2023). 70-80% of women experience subjective symptoms that can negatively affect their quality of life in their personal, social, and professional lives (Giannini et al, 2021).…”
Section: The Significance Of the Studymentioning
confidence: 99%